Representasi Krisis Kemanusiaan dalam Foto Cerita “Kelaparan di Somalia” Karya James Nachtwey - Chacha Septha Rizkha; Aliasan .; Anang Walian (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study analyzes the representation of humanitarian crisis in the photo story “Famine in Somalia” by James Nachtwey using the semiotic approach of Roland Barthes. This research applies a descriptive qualitative method with Barthes’ three levels of meaning: denotation, connotation, and myth. The data consist of seven selected photographs from the 1992 series, collected through observation, documentation, and literature review.The findings show that at the denotative level, the images depict famine victims’ physical conditions, including emaciated bodies and barren environments. At the connotative level, they represent suffering, helplessness, and social inequality. At the myth level, the photos construct the idea that humanitarian crises are shaped not only by natural factors but also by political failure and global injustice.Overall, the study highlights that photojournalism functions as visual documentation, social criticism, and a medium to evoke public awareness and empathy toward humanitarian issues.